Devising approaches to stimulating economic diversification and promoting value added production, including through investment, with a view to providing equal economic opportunity for all, particularly women and youth (UN New YorkUS, 2015)
Presents the changing sectoral composition of value added and employment in the past four decades, showing progress and setbacks. Reviews recent trends in industrial policies and discusses some key challenges in the formulation and implementation of policies aimed at sustainable and inclusive development.
Note by the UNCTD Secretariat.